1994
DOI: 10.1590/s0006-87051994000100007
|View full text |Cite
|
Sign up to set email alerts
|

Resistência a bruquídeos, composição em ácidos graxos e qualidade de cozimento das sementes em genótipos de grão-de-bico

Abstract: O presente trabalho teve por objetivos: (a) verificar possíveis diferenças entre seis genótipos de grão-de-bico (Cicer arietinum L.), selecionados no Instituto Agronômico, quanto à suscetibilidade ao ataque de Callosobruchus phaseoli (Gyllenhal), C. maculatus F. e Acanthoscelides obtectus (Say), pragas de armazenamento dessa fabácea; (b) relacionar as diferenças em suscetibilidade com a composição química das sementes, e (c) avaliar a qualidade de cozimento das sementes dos genótipos com características agronô… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Southgate (1979) reported that seed hardness, small seed size, absence of nutritional factors, and presence of toxic substances may affect bruchid damage to legume seeds. In addition, Athiepacheco et al (1994) indicated that the resistance to bruchids in chickpea may be related to tegument components as pigments in dark tegument accessions, and to the presence of linoleic acid, affecting oviposition and also larval feeding or larval biology. In antibiosis test of chickpea accessions carried out by Lema (1994), beetles laid most of their eggs on cultivars having smooth seed coat, and displayed a strong non-preference for accessions with morphologically rough seed coat.…”
Section: Chickpea Types Accessionsmentioning
confidence: 99%
“…Southgate (1979) reported that seed hardness, small seed size, absence of nutritional factors, and presence of toxic substances may affect bruchid damage to legume seeds. In addition, Athiepacheco et al (1994) indicated that the resistance to bruchids in chickpea may be related to tegument components as pigments in dark tegument accessions, and to the presence of linoleic acid, affecting oviposition and also larval feeding or larval biology. In antibiosis test of chickpea accessions carried out by Lema (1994), beetles laid most of their eggs on cultivars having smooth seed coat, and displayed a strong non-preference for accessions with morphologically rough seed coat.…”
Section: Chickpea Types Accessionsmentioning
confidence: 99%
“…Bruchid resistance has been studied in other legume crops where wild relatives are the main source of resistance (Aznar-Fernández et al, 2017; Mishra et al, 2018). Nonetheless, some sources of resistance have also been identified in cultivated species such as in Vigna mungo (L.) Hepper (black gram) (Dongre et al, 1996), Cicer arietinum L. (chickpea) (Athiepacheco et al, 1994; Shaheen et al, 2006), Phaseolus vulgaris L. (common bean) (Ishimoto and Chrispeels, 1996; Goossens et al, 2000), Vigna unguiculata (L.) Walp. (cowpea) (Redden et al, 1983; Adam and Baidoo, 2008), V. radiata (L.) R. Wilczek (mungbean) (Schafleitner et al, 2016), Pisum sativum L. (pea) (Morton et al, 2000; Clement et al, 2002), or Cajanus cajan (L.) Millsp.…”
Section: Introductionmentioning
confidence: 99%